Effect of sintering temperature, additive ratios, and reinforcement of boron and boron carbide particle sizes on the mechanical and tribological properties of the synthesized Cu-Cr hybrid composites - Kara, Gamze Ispirlioglu; Sezek, Sinan; Aksakal, Bunyamin; Macit, Cevher Kursat; Horlu, Merve (Elsevier Sci Ltd, 2024)
In this study, hybrid composites were generated by combining Copper (Cu) powder with Chromium (Cr) powder at a fixed weight of 1 %, as well as Boron (B) and Boron carbide (B4C) powders at specific weight ratios (1 %, 2 %, 3 %, and 4 %), with variable particle sizes (1 mu m and 44 mu m). Powder metallurgy production parameters were employed to produce two sets of samples at sintering temperatures of 750 degrees C and 850 degrees C. Analysis of the microstructure of the samples was performed, as well as hardness and abrasion tests. A variety of B/B4C ratios and particle diameters were employed to characterize Cu-based hybrid composites using SEM-EDS and XRD. Weight loss graphs and coefficient of friction values were generated for each sample subsequent to wear tests. The results of the tests indicated a 76.25 % increase in hardness values with B reinforcement and a 60.71 % increase with B4C reinforcement in comparison to a pure Cu sample. As the sintering temperature increased and the size of the reinforcement particles decreased, the hardness of the material increased, resulting in identical results in the wear testing. A tribo-layer was observed to have formed between the wear pin and the samples in the new hybrid composites with Boron matrix in the SEM images taken after wear. The wear resistance properties of Cu matrix hybrid composites were found to be enhanced by this tribolayer.
Keywords: Powder metallurgy; Hybrid Composites; Copper; Boron and Boron Carbide; Tribology